2003
DOI: 10.1203/01.pdr.0000061562.67041.c0
|View full text |Cite
|
Sign up to set email alerts
|

Transient Intrauterine Hypotension Causes Apoptosis in Fetal Rat Brain and Affects Learning

Abstract: Hypotensive episodes are frequent during pregnancy, and their functional effect on fetal brain has not been studied. We produced systemic hypotension for 30 min during mid-gestation in pregnant rats and examined their offspring on postnatal days 1 and 28. When compared with sham controls, the brain of the hypotensive group contained more TUNEL-positive cells in the hippocampal and periventricular regions on both time points. Spatial learning assessed by water milk maze test was impaired in 28-day-old pups of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 22 publications
3
5
0
Order By: Relevance
“…To model this physiological phenomenon that occurs during the natural course of pregnancy, maternal hypotension was induced on the 15 th day of pregnancy in rats and we sacrificed animals on the 17 th day and 19 th day (late term) of the pregnancy, representing the last trimester of human pregnancy. In our previous study in which a similar hypotension protocol was used, we demonstrated increased apoptosis in newborn rat brains on postnatal days 1 and 28 (10). Furthermore, increased apoptosis on postnatal day 28 was positively correlated with the impairment of spatial learning, highlighting the clinical significance of hypoxic/ischemic injury in late pregnancy.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations
“…To model this physiological phenomenon that occurs during the natural course of pregnancy, maternal hypotension was induced on the 15 th day of pregnancy in rats and we sacrificed animals on the 17 th day and 19 th day (late term) of the pregnancy, representing the last trimester of human pregnancy. In our previous study in which a similar hypotension protocol was used, we demonstrated increased apoptosis in newborn rat brains on postnatal days 1 and 28 (10). Furthermore, increased apoptosis on postnatal day 28 was positively correlated with the impairment of spatial learning, highlighting the clinical significance of hypoxic/ischemic injury in late pregnancy.…”
Section: Discussionmentioning
confidence: 63%
“…The duration and severity of hypotension may also contribute to the distribution of brain injury, as demonstrated by us and others (3,10,29,30). Clamping of the umbilical cord for 10 minutes caused an injury predominantly in the telencephalon region (29); shorter but repeated episodes (5 minutes, four times) of umbilical cord occlusion damaged the striatum (30).…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Low blood pressure and syncopal episodes during pregnancy have been reported to alter fetal perfusion and are associated with increased rates of stillbirth, preterm deliveries, and low birth weight (3)(4)(5)(6). As demonstrated by previous research, perfusion failure during pregnancy causes HI injury to the fetal brain (7)(8)(9), which may subsequently result in fetal brain malformations and increased morbidity and mortality (10)(11)(12).…”
Section: Introductionmentioning
confidence: 89%